Rola liderek w zmieniających się paradygmatach organizacji - Przyborowska, Beata (Studia Edukacyjne, 2023)
The text adopts the perspective of D. Back’s Spiral Dynamics model, which was used by F. Laloux to search for a new optimal organizational model that would change the contemporary organizational reality. The text presents the evolution of women’s leadership paradigms depending on the type of organization in which they operate. Answers were sought to the following questions: How do women leaders find themselves in different organizational paradigms? What opportunities and risks are associated with their functioning in the organization depending on its paradigm? Does women’s leadership change its meaning and lose its specific character, with the development of human individual and social consciousness? If so, how does it take place?